Study on Sports Industrial Share Economy in the Era Internet Plus (Global Journal of Human-Social Science, 2017)
Internet and sharing economy as a cutting edge the hottest in the two kinds of development model for the development of Chinese sports industry is relatively stable progress and breakthrough in terms of the status quo of small is undoubtedly a good opportunity Combining both advantages seize the opportunity to improve the process of sports development China is now the key to the development of Chinese sports This article is based on Internet sharing economy and the relationship of sports industry construct a new framework for the development of sports industry First of all from the perspective of the relationship between it is pointed out that making full use of taobao pay treasure all kinds of online payment platform weibo We Chat sohu and other micro culture build Internet sports apparel sports services sports fitness equipment sporting events such as development pattern can trigger the birth of the new energy new power sports development And the integration of sharing economy make the sports industry development from product research and development through product sales to consumers hands and realize the sharing between different brand to avoid the development gap because of the competition for the present development of Chinese sports to create a new development environment finally achieve common development of sports industry whole industry comprehensively promotes the prosperity of
Keywords: internet; sharing economy; sports industry